Babes in Toyland [videorecording (Blu-Ray)] - Barrymore, Drew; Reeves, Keanu; Mulligan, Richard, 1932-2000; Brennan, Eileen; Morita, Pat, 1932-2005 (Kino Lorber, 2023)
Once a bright and cheerful community, Toyland is in great danger from the terrible Barnaby and his scary creatures who live in the forest of the night. The only person who can save Toyland is Lisa, a little girl from Cincinnati who lands in Toyland on Christmas Eve. But since Lisa, a very ₃grown-up₄ little girl, doesn't believe in toys, she needs special help from the wise but impish Toymaster, the dashing and gallant Jack Nimble, and the mother-of-many-children Mrs. Hubbard. Together they muster an army of toy soldiers and teddy bears to drive the villainous Barnaby and his nightmare creatures out of Toyland!